2011
DOI: 10.1371/journal.pone.0024783
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Gene Expression of Factors Related to Lipid Processing in Obesity

Abstract: BackgroundAdipose tissue lipid storage and processing capacity can be a key factor for obesity-related metabolic disorders such as insulin resistance and diabetes. Lipid uptake is the first step to adipose tissue lipid storage. The aim of this study was to analyze the gene expression of factors involved in lipid uptake and processing in subcutaneous (SAT) and visceral (VAT) adipose tissue according to body mass index (BMI) and the degree of insulin resistance (IR).Methods and Principal FindingsVLDL receptor (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 39 publications
7
61
1
2
Order By: Relevance
“…Supporting these assumptions, we did not observe significant differences between groups in mRNA level of markers of nonadipocyte cells, suggesting no interference of other cell types with the DNA quantification procedure. Furthermore, the decreased Fabp4 expression in mice receiving the HF-D diet is in agreement with an IR state, fat cell hypertrophy, and changes in body composition as described in humans (25,26).…”
Section: Figsupporting
confidence: 82%
“…Supporting these assumptions, we did not observe significant differences between groups in mRNA level of markers of nonadipocyte cells, suggesting no interference of other cell types with the DNA quantification procedure. Furthermore, the decreased Fabp4 expression in mice receiving the HF-D diet is in agreement with an IR state, fat cell hypertrophy, and changes in body composition as described in humans (25,26).…”
Section: Figsupporting
confidence: 82%
“…Lipolysis of TG-rich lipoproteins is impaired in obesity by reduced expression of lipoprotein lipase (LPL) mRNA in adipose tissue [3]. Elevated TG induces delayed clearance of TG-rich lipoproteins, and increases formation of small dense LDL [4][5][6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Age was not also significantly correlated with change in serum TG (r = -0.04, P = 0.62) in all participants including obese and non-obese patients. Body weight loss may ameliorate insulin resistance, and subsequently may increase expression of LPL which led to reduction in TG among obese people [2,3,18]. To understand the effects of sitagliptin on serum lipids precisely and validly, further studies, preferably with larger numbers of subjects in fasting state, will be needed.…”
Section: Discussionmentioning
confidence: 99%
“…The same principle applies to humans: those with VLDLR gene mutations have lower body weight compared with the control group (Boycott et al, 2005;Crawford et al, 2008). Therefore, VLDLR were confirmed to be associated with body weight and obesity in humans and mice (Brockmann et al, 1998;Kunej et al, 2012;Clemente-Postigo et al, 2011). In overweight humans, it was observed that VLDLR were significantly upregulated and their expression levels were probably closely linked to the molecular markers of obesity phenotype (Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 98%